2021
DOI: 10.3390/nu14010173
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation throughout Life with Non-Digestible Oligosaccharides and/or n-3 Poly-Unsaturated Fatty Acids in Healthy Mice Modulates the Gut–Immune System–Brain Axis

Abstract: The composition and activity of the intestinal microbial community structures can be beneficially modulated by nutritional components such as non-digestible oligosaccharides and omega-3 poly-unsaturated fatty acids (n-3 PUFAs). These components affect immune function, brain development and behaviour. We investigated the additive effect of a dietary combination of scGOS:lcFOS and n-3 PUFAs on caecal content microbial community structures and development of the immune system, brain and behaviour from day of birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…It is known that the change in the distribution and in the number of ECs can depend on the diet type and the gut microbiota [ 110 , 111 ]. These authors studied the health status of pigs fed with a rye-type and hybrid rye-type grains, and they showed that neither of the rye grains modified the homeostasis and the somatostatin production by neuroendocrine cells.…”
Section: Enterochromaffin Cells and Diet In Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the change in the distribution and in the number of ECs can depend on the diet type and the gut microbiota [ 110 , 111 ]. These authors studied the health status of pigs fed with a rye-type and hybrid rye-type grains, and they showed that neither of the rye grains modified the homeostasis and the somatostatin production by neuroendocrine cells.…”
Section: Enterochromaffin Cells and Diet In Pathologymentioning
confidence: 99%
“…These authors studied the health status of pigs fed with a rye-type and hybrid rye-type grains, and they showed that neither of the rye grains modified the homeostasis and the somatostatin production by neuroendocrine cells. These results are important in a wider strategy for developing a new nutritional plan for pigs [ 110 ]. Successively, the same authors evaluated the number of the ECs in the small intestine of suckling piglets stimulated with red kidney bean lectin [ 111 ].…”
Section: Enterochromaffin Cells and Diet In Pathologymentioning
confidence: 99%
“…Nutrition appears as an interesting innovative approach for preventing or delaying the development of age-related cognitive social behavior deficits by targeting microbiota [24]. Indeed, several studies reported the effects of nutrition on gut microbiota, notably peptides and omega-3 PUFAs [25][26][27][28][29][30]. We previously demonstrated that dietary supplementation with a fish hydrolysate containing low-molecular-weight peptides and n-3 LC-PUFAs effectively prevent age-related spatial short-term memory deficits and influence navigation strategies during spatial learning [31].…”
Section: Introductionmentioning
confidence: 99%